HIPOTIROID KONGENITAL DAN GANGGUAN PENDENGARAN - ADITYA NUGRAHA, IDA BAGUS; PRADIPTHA, I PUTU YUPINDRA (Ganesha Medicina, 2023)
Congenital hypothyroidism is a cause of physical and mental disabilities that can be prevented with early detection and therapy. However, early diagnosis is difficult to enforce clinically because most newborns with congenital hypothyroidism do not show any typical symptoms. Permanent hearing loss has been reported in patients with congenital hypothyroidism who were not detected early and treated late until 6 months of age. This is different from hearing loss caused by acquired hypothyroidism, in which symptoms of hearing loss can be corrected by treating hypothyroidism. The central nervous system is one of the most affected by congenital hypothyroidism and can cause behavioral, language, and social difficulties in a child's development. Congenital hypothyroidism, if not treated adequately, can cause serious behavioral problems whereas over-therapy of congenital hypothyroidism appears to be associated with impaired attention. Therefore, treatment should be based on clinical sign and symptoms, regular monitoring of clinical conditions and health promotion strategies to improve not only treatment adherence but also the long-term prognosis of hearing loss.